Supramolecular materials based on AIE luminogens (AIEgens): construction and applications - Li, Jie; Wang, Jianxing; Li, Haoxuan; Song, Nan; Wang, Dong; Tang, Ben Zhong (Chemical Society reviews, 2020)
The emergence of aggregation-induced emission luminogens (AIEgens) has significantly stimulated the development of luminescent supramolecular materials because their strong emissions in the aggregated state have resolved the notorious obstacle of the aggregation-caused quenching (ACQ) effect, thereby enabling AIEgen-based supramolecular materials to have a promising prospect in the fields of luminescent materials, sensors, bioimaging, drug delivery, and theranostics. Moreover, in contrast to conventional fluorescent molecules, the configuration of AIEgens is highly twisted in space. Investigating AIEgens and the corresponding supramolecular materials provides fundamental insights into the self-assembly of nonplanar molecules, drastically expands the building blocks of supramolecular materials, and pushes forward the frontiers of supramolecular chemistry. In this review, we will summarize the basic concepts, seminal studies, recent trends, and perspectives in the construction and applications of AIEgen-based supramolecular materials with the hope to inspire more interest and additional ideas from researchers and further advance the development of supramolecular chemistry. This review presents comprehensive discussions on the recent development in supramolecular materials based on luminogens with aggregation-induced emission (AIE) characteristics.